Efficient Charge Separation of In‐Situ Nb‐Doped TiO2 Nanowires for Photoelectrochemical Water–splitting. Issue 9 (28th March 2017) - Tian, Zhangliu; Cui, Houlei; Xu, Jijian; Zhu, Guilian; Shao, Feng; He, Jianqiao; Huang, Fuqiang
Abstract: One‐dimensional TiO2 nanowire is the top‐performing semiconductor among photoanodes for photoelectrochemical water splitting, but still limited to a fraction of the theoretically photocurrent because of modest charge transport and low charge separation properties. Here, we demonstrate high‐crystallized nanowires of Nb‐doped rutile TiO2 for significantly increasing electron carrier density through a convenient method. The optimized Nb‐doped TiO2 nanowires (0.5 mol% in the Nb/Ti ratio) yield a high value of charge separation efficiency (ηsep ) of 97.39% at 1.23 VRHE, which is about 3 times as much as that of pristine sample (33.61% at 1.23 VRHE ). Moreover, the photoanode of Nb‐doped TiO2 nanowires can achieve high charge transfer efficiency (ηtrans ) (91.07% at 1.23 VRHE ) without any oxygen evolution reaction catalysts. These results indicate that through appropriate amount of Nb doping can move the performance of TiO2 nanowires to their theoretical potential. Abstract : Through a suitable amount of NbCl5 added in the reaction liquid, we have successfully realized the controlled doping of Nb into high‐crystallized TiO2 NWs. This is a simple and effective method which can greatly improve the ηsep to overcome the intrinsically poor charge transport properties of TiO2, thereby achieving ηsep of 73.91% at 0.6 VRHE and 97.39% at 1.23 VRHE for Nb/TiO2 ‐0.5, which is one of the highest ηsep for TiO2 photoanodes.